No miR Quirk: Dysregulation of microRNAs in Pancreatic Ductal Adenocarcinoma - Y. Cheung, Philip; E. Szafranska-Schwarzbach, Anna; M. Schlageter, Annette; F. Andruss, Bernard; J. Weiss, Glen (MicroRNA, 2012)
MicroRNAs are post-transcriptional regulators of gene expression with tissue-specific expression profiles. Dysregulation of microRNAs has been shown to play a role in carcinogenesis. Although progress has been made in the diagnosis and treatment of many cancers, pancreatic cancer remains an intractable public health problem, causing 6.58% of cancer deaths despite making up less than 3% of cancer diagnoses in the United States. No screening, diagnostic or imaging techniques exist with the sensitivity to detect pancreatic cancer in its early, operable stages. Risk factors include numerous inherited syndromes, diabetes mellitus, and hepatitis C virus infection. Here we review the literature regarding dysregulation of microRNA expression in native pancreas, pancreatic ductal adenocarcinoma (the dominant form of pancreatic cancer), and its risk factors to illuminate the biology and progression of this disease. We explore promising evidence for the use of microRNAs as prognostic and diagnostic tools, and discuss emerging reports on microRNA therapeutics.
Keywords: Biomarker